Enhancing surface hydrophobicity of AISI 304 stainless steel via laser texturing - M. Isa, Rahim; Syarifah Nur Aqida, Syed Ahmad; Salwani, Mohd Salleh; Ahmad Syahrizan, Sulaiman (IOP Publishing, 2025)
The wettability performance of 304 stainless steel surfaces that were treated by multipulse laser processing under different parameters is studied in this paper. For modifying the surface of stainless steel, we used an x-y computer numerical control (CNC) fibre laser system with a 1064 nm wavelength. The hydrophobicity of all surfaces was evaluated through water contact angles (WCA) at different translational speeds (20–150 mm/s) and laser powers (4–20 W). Results show a spectrum of surface wettability ranging from hydrophilic (WCA<90°) to hydrophobic properties (90<WCA<150°). Hydrophobic surfaces were mainly associated with the samples processed at higher speeds and power settings while hydrophilic results were observed due to lower speeds and power settings. The highest hydrophobicity of WCA = 142.05° was obtained at a speed of 20 mm/s and laser power of 8 W. Meanwhile, the highest degree of hydrophilicity was observed at a speed of 20 mm/s and the lowest power level of 4 W, which possessed a WCA of 62.49°. Therefore, this study highlights the importance of laser parameters in the surface wettability modification process. These results are significant to applications requiring specific surface characteristics, such as anti-slip, anti-fog and self-cleaning. The findings provide a comprehensive review of the application of laser processing in preparing surface treatment with suitable properties for various industrial and biomedical applications.